Forms of Care: Chimamanda Ngozi Adichie’s Americanah (2014), Agency, and Decolonial Feminism - McCann, Fiona (Études littéraires africaines, 2021)
Cet article explore la politique féministe telle qu’elle est représentée dans le roman Americanah de Chimamanda Ngozi Adichie, ainsi que la manière dont ce féminisme s’entremêle avec des formes de care. Je cerne les contours de l’engagement affiché de l’autrice pour le féminisme intersectionnel, tout en pointant quelques angles morts. Après avoir situé l’oeuvre d’Adichie dans le contexte des féminismes postcolonial, populaire et décolonial, j’étudie l’importance des cheveux et la question plus générale de l’agentivité. Dans la dernière partie, je démontre que la poétique du care développée dans le roman n’adhère pas totalement au féminisme décolonial en raison de l’invisibilité relative des structures néo-coloniales à l’oeuvre au Nigeria pendant la période contemporaine.
Keywords: afro-féminisme; agentivité; approches et analyses; arts; care; discipline; féminisme décolonial; féminismes noirs; littérature; militance; politique; ressource en ligne; thématiques; études littéraires

Indigenous women and feminism: politics, activism, culture - Suzack, Cheryl; Huhndorf, Shari M.; Perreault, Jeanne; Barman, Jean (Women and indigenous studies series, 2010)
"Can the specific concerns of Indigenous women be addressed within current mainstream feminist and post-colonial discussions? Indigenous Women and Feminism: Politics, Activism, Culture proposes that a dynamic new line of inquiry -- Indigenous feminism -- is necessary to truly engage with the crucial issues of cultural identity, nationalism, and decolonization particular to Indigenous contexts. Through the lenses of politics, activism, and culture, this wide-ranging collection examines the historical roles of Indigenous women, their intellectual and activist work, and the relevance of contemporary literature, art, and performance for an emerging Indigenous feminist project. The questions at the heart of these essays -- What is at stake in conceptualizing Indigenous feminism? How does feminism relate to Indigenous claims to land and sovereignty? What lessons can we learn from the past? How do Indigenous women engage ongoing violence and social and political marginalization? -- cross disciplinary, national, academic, and activist boundaries to explore in depth the unique political and social positions of Indigenous women."--Page 4 de la couverture."A vital and sophisticated discussion that will change the way we think about modern feminism, Indigenous Women and Feminism will be invaluable to scholars, activists, artists, community organizers, and those concerned with Indigenous and feminist issues at home and abroad."-- Résumé de l'éditeur.
Keywords: activisme; approches et analyses; arts; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; militance; pol4105; premier cycle; premières nations; système colonial; systèmes d'oppressions; territoire; thématiques; études autochtones; études féministes; études littéraires

Dangerous liaisons: gender, nation and postcolonial perspectives - McClintock, Anne; Shohat, Ella; Mufti, Aamir Rashid (Cultural politics, 1997)
This collection addresses the issues raised by the postcolonial condition, considering nationhood, history, gender and identity from an interdisciplinary perspective.
Keywords: LGBTQIA2+; approches et analyses; arts; cours; discipline; discours dominant; féminisme décolonial; histoire et politique; identités LGBTQIA2+; intersectionnalité; inégalités; lit4700; militance; poésie; premier cycle; queer; racisme; sexisme; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Je suis une maudite sauvagesse = Eukuan nin matshimanitu innu-iskueu - Antane Kapesh, An (Leméac, 1976)
An Antane Kapesh signe un réquisitoire accablant contre les Blancs : « Quand le Blanc a voulu exploiter et détruire notre territoire, il n'a demandé de permission à personne, il n'a pas demandé aux Indiens s'ils étaient d'accord. »
Keywords: amériques; approches et analyses; autochtones; cours; discipline; fem1000; fem3100; femmes* innues; féminisme décolonial; littérature; manifeste; militance; pol4105; pol5480; premier cycle; premières nations; québec; racisme; racisme systémique; régions géographiques; systèmes d'oppressions; thématiques; études littéraires